THE INTERSECTION OF POLYHEDRA WITH A PLANE. (International journal of artificial intelligence, 2026)
This article analyzes the spatial-geometric properties of polyhedra and the theoretical foundations of their intersection with a plane. The definition of a polyhedron, its main elements (faces, edges, vertices), and its types are scientifically explained using examples of prisms, pyramids, and regular polyhedra. The property that the cross-section formed by intersecting a convex polyhedron with a plane is itself a convex polygon is substantiated through geometric and analytical approaches.